Line 5: Line 5:
 
[[Category:signal processing]]   
 
[[Category:signal processing]]   
  
<center><font size= 5>
+
<center>
Inverse Z Transform *under construction*
+
==Inverse Z Transform *under construction*==
</font size></center>
+
</center>
  
<font size= 4>
 
  
Overview
+
'''Introduction'''
<font size= 3>
+
:The purpose of this page is to...
+
: I. Define the Z Transform and Inverse Z Transform
+
: II. Provide Example Problems of the Inverse Z Transform
+
</font size>
+
  
<font size= 4>
+
The Z Transform is the generalized version of the DTFT. This is done by replacing <math>e^{j\omega}</math> with <math> re^{j\omega} = z </math>. The DTFT is equal to the Z Transform when <math>|z| =1 </math>  
I. Definitions
+
</font size>  
+
  
<font size= 3>
+
<math>
: Z Transform
+
\begin{align}
<center>
+
\text{DTFT: }
<math>X(z)=\mathcal{L}(x[n])=\sum_{n=-\infty}^{\infty}x[n]z^{-n}</math>
+
 
</center>
+
X(w) &= \sum_{n=-\infty}^\infty x[n]e^{-j\omega n}\\
: Inverse Z Transform
+
 
<center>
+
\text{Z-Transform: }
<math>x[n]=\mathcal{L}^{-1}(X(z))=\frac{1}{2\pi j}\oint_{c}X(z)z^{n-1}dz</math>
+
   
</center>
+
X(z) &= \sum_{n=-\infty}^\infty x[n]z^{-n}\\
 +
 
 +
\text{Inv. Z-Transform: }
 +
   
 +
x[n] &= \frac{1}{2\pi j}\oint_{c}X(z)z^{n-1}dz
 +
 
 +
\end{align}
 +
</math>
 +
 
 +
'''Region of Convergence'''
 +
 
 +
The R.O.C. determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'.
 +
 
 +
<math>
 +
\begin{align}
 +
\text{Remember: }
 +
z &=re^{j\omega}
 +
\end{align}
 +
</math>
 +
 
 +
""II. Example Problems of the Inverse Z Transform""
  
<font size= 4>
 
II. Example Problems of the Inverse Z Transform
 
</font size>
 
  
<font size= 3>
 
 
:We will find the Inverse Z transform of various signals by manipulation and then using direct Inversion.
 
:We will find the Inverse Z transform of various signals by manipulation and then using direct Inversion.
 
:On the first example we will go slowly over each step.
 
:On the first example we will go slowly over each step.
Line 44: Line 52:
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
  
::<font size = 2>note: It is important to realize that we are not going to try to use the direct formula for an inverse Z transform, Instead our approach will be to manipulate the signal so that we can directly compare it with the Z transform equation and by inspection obtain the Inverse Z transform.</font size>
+
::note: It is important to realize that we are not going to try to use the direct formula for an inverse Z transform, Instead our approach will be to manipulate the signal so that we can directly compare it with the Z transform equation and by inspection obtain the Inverse Z transform.
  
:<font size= 2>First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z</font size>
+
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
 
<center><math>|A| < 1</math></center>
 
<center><math>|A| < 1</math></center>
  
:<font size= 2>In this case this is already satisfied with </font size>
+
:In this case this is already satisfied with  
 
<center><math>A = z</math></center>
 
<center><math>A = z</math></center>
  
:<font size= 2>Then we need to manipulate the given signal to be in the following form, B is just some expression that is the result of adjusting the equation (in this case B = 1)</font size>
+
:Then we need to manipulate the given signal to be in the following form, B is just some expression that is the result of adjusting the equation (in this case B = 1)
 
<center><math>X(z)=B\frac{1}{1-A}</math></center>
 
<center><math>X(z)=B\frac{1}{1-A}</math></center>
  
:<font size=2>Using a infinite Geometric sum we can obtain following...</font size>
+
:Using a infinite Geometric sum we can obtain following...
  
 
<center><math>X(z) = \sum_{n=0}^{\infty} 1(z^{n}) = \sum_{n=-\infty}^{\infty} z^{n} u[n]</math></center>
 
<center><math>X(z) = \sum_{n=0}^{\infty} 1(z^{n}) = \sum_{n=-\infty}^{\infty} z^{n} u[n]</math></center>
Line 61: Line 69:
 
<center><math>\text{let } k = -n \text{ then, } X(z) = \sum_{k=-\infty}^{\infty} z^{-k} u[-k]= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}</math></center>
 
<center><math>\text{let } k = -n \text{ then, } X(z) = \sum_{k=-\infty}^{\infty} z^{-k} u[-k]= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}</math></center>
  
:<font size= 2> By comparison with the Z Transform definition, we can determine <math> x[n] </math></font size>
+
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
  
 
<center><math>x[n] = u[-n]</math></center>
 
<center><math>x[n] = u[-n]</math></center>
Line 69: Line 77:
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
  
:<font size= 2>First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z</font size>
+
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
 
<center><math>|A| < 1</math></center>
 
<center><math>|A| < 1</math></center>
  
:<font size= 2>In this case</font size>
+
:In this case
 
<center><math>A = \frac{1}{z}</math></center>
 
<center><math>A = \frac{1}{z}</math></center>
  
:<font size= 2>Manipulate the given signal</font size>
+
:Manipulate the given signal
 
<center><math>X(z)=\frac{1}{1-z} = \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}</math></center>
 
<center><math>X(z)=\frac{1}{1-z} = \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}</math></center>
  
:<font size=2>Using a infinite Geometric sum we can obtain</font size>
+
:Using a infinite Geometric sum we can obtain
  
 
<center><math>X(z) =  \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} =  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} =  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]</math></center>
 
<center><math>X(z) =  \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} =  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} =  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]</math></center>
Line 84: Line 92:
 
<center><math> \text{ let } k=n+1, \text{ then } X(z) =  \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] =  \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}</math></center>
 
<center><math> \text{ let } k=n+1, \text{ then } X(z) =  \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] =  \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}</math></center>
  
:<font size= 2> By comparison with the Z Transform definition, we can determine <math> x[n] </math></font size>
+
:By comparison with the Z Transform definition, we can determine <math> x[n] </math>
  
 
<center><math>x[n] = (-1)^{n-1} u[n-1]</math></center>
 
<center><math>x[n] = (-1)^{n-1} u[n-1]</math></center>
Line 92: Line 100:
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
  
:<font size= 2>Manipulate the given signal</font size>
+
:Manipulate the given signal
  
 
<center><math>X(z)=\frac{1}{1-2z} = \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}</math></center>
 
<center><math>X(z)=\frac{1}{1-2z} = \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}</math></center>
  
:<font size=2>Using a infinite Geometric sum we can obtain</font size>
+
:Using a infinite Geometric sum we can obtain
  
 
<center><math>X(z) =  \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} = \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]</math></center>
 
<center><math>X(z) =  \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} = \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]</math></center>
Line 102: Line 110:
 
<center><math> \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}</math></center>
 
<center><math> \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}</math></center>
  
:<font size= 2> By comparison with the Z Transform definition, we can determine <math> x[n] </math></font size>
+
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
  
 
<center><math>x[n] = \frac{1}{2}(-2)^{-k+1}u[n-1]</math></center>
 
<center><math>x[n] = \frac{1}{2}(-2)^{-k+1}u[n-1]</math></center>

Revision as of 14:04, 19 December 2014


Inverse Z Transform *under construction*


Introduction

The Z Transform is the generalized version of the DTFT. This is done by replacing $ e^{j\omega} $ with $ re^{j\omega} = z $. The DTFT is equal to the Z Transform when $ |z| =1 $

$ \begin{align} \text{DTFT: } X(w) &= \sum_{n=-\infty}^\infty x[n]e^{-j\omega n}\\ \text{Z-Transform: } X(z) &= \sum_{n=-\infty}^\infty x[n]z^{-n}\\ \text{Inv. Z-Transform: } x[n] &= \frac{1}{2\pi j}\oint_{c}X(z)z^{n-1}dz \end{align} $

Region of Convergence

The R.O.C. determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'.

$ \begin{align} \text{Remember: } z &=re^{j\omega} \end{align} $

""II. Example Problems of the Inverse Z Transform""


We will find the Inverse Z transform of various signals by manipulation and then using direct Inversion.
On the first example we will go slowly over each step.

Ex. 1 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 $

note: It is important to realize that we are not going to try to use the direct formula for an inverse Z transform, Instead our approach will be to manipulate the signal so that we can directly compare it with the Z transform equation and by inspection obtain the Inverse Z transform.
First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
$ |A| < 1 $
In this case this is already satisfied with
$ A = z $
Then we need to manipulate the given signal to be in the following form, B is just some expression that is the result of adjusting the equation (in this case B = 1)
$ X(z)=B\frac{1}{1-A} $
Using a infinite Geometric sum we can obtain following...
$ X(z) = \sum_{n=0}^{\infty} 1(z^{n}) = \sum_{n=-\infty}^{\infty} z^{n} u[n] $
$ \text{let } k = -n \text{ then, } X(z) = \sum_{k=-\infty}^{\infty} z^{-k} u[-k]= \sum_{k=-\infty}^{\infty}u[-k] z^{-k} $
By comparison with the Z Transform definition, we can determine $ x[n] $
$ x[n] = u[-n] $

Ex. 2 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 $

First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
$ |A| < 1 $
In this case
$ A = \frac{1}{z} $
Manipulate the given signal
$ X(z)=\frac{1}{1-z} = \frac{1}{z} \frac{1}{1-(-\frac{1}{z})} $
Using a infinite Geometric sum we can obtain
$ X(z) = \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} = \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} = \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n] $
$ \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] = \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k} $
By comparison with the Z Transform definition, we can determine $ x[n] $
$ x[n] = (-1)^{n-1} u[n-1] $

Ex. 4 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 $

Manipulate the given signal
$ X(z)=\frac{1}{1-2z} = \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})} $
Using a infinite Geometric sum we can obtain
$ X(z) = \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} = \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n] $
$ \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k} $
By comparison with the Z Transform definition, we can determine $ x[n] $
$ x[n] = \frac{1}{2}(-2)^{-k+1}u[n-1] $

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett